Mongolia Economic Update, February 2021 : From Relief to Recovery - World Bank (World Bank, Ulaanbaatar, 2021)
Strict implementation of social distancing, mobility restrictions, and quarantine measures have helped Mongolia contain the worst health effects of the Coronavirus (COVID-19) pandemic, though the country remains in the midst of a significant outbreak. The economic impact of the Coronavirus (COVID-19) pandemic has been severe and widespread. The Coronavirus (COVID-19) shock also affected the structure and conditions of the labor market. Mongolia, like other countries, will need to transition from policies focused on short-term economic relief to accelerating recovery and building resilience. The challenge Mongolia faces in this regard is that the fiscal space to continue the generous support policies enacted during 2020 is quite limited, while their rapid withdrawal as long as the economy remains weakened by public-health-related mobility restrictions could create significant difficulties for households and firms. Another priority is to prevent the Coronavirus (COVID-19) shock from undermining financial stability. Finally, Mongolia should adopt an integrated and fiscally sustainable approach to boosting medium-term economic prospects and job creation.